2020
DOI: 10.1108/sampj-05-2018-0136
|View full text |Cite
|
Sign up to set email alerts
|

The impact of board composition on the level of ESG disclosures in GCC countries

Abstract: Purpose This paper aims to investigate the impact of board composition on environmental, social and governance (ESG) reporting in the Gulf countries. Despite the vast literature on the significance of ESG disclosure on firms’ performance, trust and reputation, there are relatively few studies on the influence of board structure on ESG disclosure in the Gulf Cooperation Council (GCC) countries. Gulf countries are witnessing a fast growing capital markets and having serious efforts to attract foreign investments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
272
4
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(314 citation statements)
references
References 106 publications
(144 reference statements)
34
272
4
4
Order By: Relevance
“…With the growing importance of CSR, recent studies proposed that independent directors may also align the interests of firms with those of stakeholders (Gallego-Álvarez & Pucheta-Martínez, 2020), and tested this proposition by incorporating board independence in CSR studies. However, the findings are inconclusive; some studies found that board independence improves CSR engagement (Arayssi et al, 2019;Gallego-Álvarez & Pucheta-Martínez, 2020), others found that it decreases (Adel, Hussain, Mohamed, & Basuony, 2019), and still others found a neutral effect (Michelon & Parbonetti, 2012). Therefore, our study provides additional evidence of the influence of independent directors on CSRP.…”
Section: Findings and Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…With the growing importance of CSR, recent studies proposed that independent directors may also align the interests of firms with those of stakeholders (Gallego-Álvarez & Pucheta-Martínez, 2020), and tested this proposition by incorporating board independence in CSR studies. However, the findings are inconclusive; some studies found that board independence improves CSR engagement (Arayssi et al, 2019;Gallego-Álvarez & Pucheta-Martínez, 2020), others found that it decreases (Adel, Hussain, Mohamed, & Basuony, 2019), and still others found a neutral effect (Michelon & Parbonetti, 2012). Therefore, our study provides additional evidence of the influence of independent directors on CSRP.…”
Section: Findings and Discussionmentioning
confidence: 56%
“…the authors attribute this situation to the immaturity or small proportion of CSR committees in the sampled firms (Michelon & Parbonetti, 2012). Past evidence also indicated that CSR committees are influential in fostering CSR practices of firms in emerging countries (Arayssi et al, 2019;Gallego-Álvarez & Pucheta-Martínez, 2020). As sectoral evidence, Uyar et al (2020) proved that logistics firms with CSR committees are more likely to publish a higher number of CSR reports over the years.…”
Section: Findings and Discussionmentioning
confidence: 94%
“…However, the moderating role of ESG controversies on the relationship between board gender diversity and ESG performance is not evident. This study contributes to the literature of gender diversity (Birindelli et al, 2019;Manita et al, 2018) and ESG by postulating empirical evidence (Arayssi et al, 2020;Cucari et al, 2018) that the participation of female members on the board considerably affects the ESG performance of banks. The positive association between gender diversity and ESG performance support the resource dependence theory by exhibiting women's background, psychological characteristics and experience as critical resources for banks (Kyaw et al, 2017); and these intellectual and interpersonal attributes of women directors assist them to achieve the legitimate performance in ESG (Jizi, 2017).…”
Section: Introductionmentioning
confidence: 88%
“…In general, board members take the strategic decision like ESG. Female board members are concerned than their male counterparts regarding ESG welfare (Arayssi et al, 2020), and they consider ESG controversies seriously.…”
Section: Moderating Effects Of Esg Controversies On the Relationship mentioning
confidence: 99%
“…Thomson Reuters Eikon database, which is commonly used in the literature (Arayssi, Jizi, & Tabaja, 2020). Ragin (2000Ragin ( , 2008, traditional statistical methods such as regression propose that the impacts found are necessary and enough to predict the outcome, while most of the actual relationships are asymmetrical.…”
Section: Variablesmentioning
confidence: 99%